2013
DOI: 10.3116/16091833/14/2/85/2013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal autolocalization of femtosecond light pulses in the filaments observed in fused silica

Abstract: Abstract.We observe temporal self-compression of the axial component of femtosecond laser pulse in the filamentation regime in fused silica and find optimized conditions for the maximum compression. Using spatial filtration, we extract the axial component of the pulse compressed down to the duration of 63 fs from the initial 160 fs one. The compressed pulse can be used as a probe in pump-probe measurements to improve their temporal resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Earlier, we recorded several spectacular phenomena accompanying the formation of fs filaments in transparent Kerr media such as the temporal self-compression of a fs pulse in filaments [3], phase-dependent repulsive and attractive interactions of two intersecting fs filaments [4][5][6], longitudinal periodicity, which appears in the luminescence of an axial plasma column of filaments in anisotropic crystal media [7].…”
Section: Early Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we recorded several spectacular phenomena accompanying the formation of fs filaments in transparent Kerr media such as the temporal self-compression of a fs pulse in filaments [3], phase-dependent repulsive and attractive interactions of two intersecting fs filaments [4][5][6], longitudinal periodicity, which appears in the luminescence of an axial plasma column of filaments in anisotropic crystal media [7].…”
Section: Early Studiesmentioning
confidence: 99%
“…In [3], the autocorrelator trace of low-energy femtosecond laser pulses with = 0.5 J, which propagate in a fused silica sample was obtained. We showed that an increase of the pulse energy up to = 2 J causes the self-focusing and appearance of a temporally compressed component in the output pulses.…”
Section: Early Studiesmentioning
confidence: 99%